Detergent induced pollen sterility in some vegetable crops - Chauhan, S. V. S.; Agnihotri, D. K. (International Journal of Horticultural Science, 2005)
Efficacy of a popular synthetic detergent, Surf excel in some important vegetable crops viz. Okra or lady finger (Abelmoschus esculentus L.), chilli or red pepper (Capsicum annuum L.) and tomato (Lycopersicon esculentum Mill) was evaluated for inducing male sterility and hybrid seed production. Foliar sprays with aqueous solutions of Surf excel (1.0 and 1.5% w/v) in these crops induced complete pollen sterility. The treated plants showed a delay in flowering, a reduction in the number of flowers and fruits/plant, number of seeds/fruit resulting in a reduction in yield/plant. However, the male sterility thus induced was successfully exploited for hybrid seed production.